Analysis of School Readiness in the Application of Visual, Auditory, and Kinesthetic-Based Differentiated Learning in Accounting Subject - Selvia Puput Anggraini; Supri Wahyudi Utomo; Elana Era Yusdita (Cita konsultindo, 2025)
Abstract This study aims to determine the readiness of SMK Negeri 2 Jiwan in applying differentiated learning based on VAK (Visual, Auditory, and Kinesthetic) learning styles in accounting subject. The method used for this research is qualitative descriptive, with data collection techniques such as in-depth interviews, classroom observations, and documentation. Informants consisted of the principal, vice principals of curriculum and school infrastructure, accounting teachers of grades X-XII, and students of various levels. The results showed that the school had demonstrated initial commitment through the implementation of Merdeka Curriculum and encouragement of learning innovations. Teachers understood the concept of differentiation, but its application was still limited and not equipped with a systematic mapping of students' learning styles. Teaching tools and learning media available did not fully support the VAK learning style, and practice facilities were inadequate. The school environment was considered to be quite supportive, though further teacher training, provision of interactive learning media, and continued assistance are still needed. In general, the school's readiness is at an early stage, and requires improvement in the aspect of implementation strategies. Aspects of readiness include teachers' understanding, curriculum, infrastructure, and learning environment.